TRANSFORMASI KELEMBAGAAN KECAMATAN DILEMA ANTARA TUNTUTAN DAN BATAS KEWENANGAN - Mukhlis, Maulana (FIAT JUSTISIA)
Position and authority of the sub-district (head-sub district) underwent a fundamental change since the regional autonomy. Huge demands from society about function in government districts, and community development are not comparable with the authority. Therefore, the formulation of the problem in this research is how the position should be owned by institutional strengthening efforts districts governance? This study aims to determine the capacity (typology) sub-districts, the pattern of organization of districts governance in the middle of the dilemma between the demands of authority boundaries. By measuring the capacity which is owned by the sub-district (budget, authority, infrastructure and human resources) in the administration of sub-district governance so far, can be explained that the problem faced by most sub-districts in Indonesia (or at least in the study area -Mesuji District-) is the narrowness of the V space which shows the capacity owned by the sub-district to be able developing governmental functions, and social development is very marginal. Nevertheless, the majority of people assume that the presence of sub-district is expected to serve in an effort to bring citizens to the state.  This condition was also aggravated by the fact that the regents did not give up the authority of distributive and attributive of its authority to the head of sub-district and sub-district institutions as possible in Article 126 of Law 32/2004. Politically, the reluctance to distribute this authority shows that the delegation of authority to the head of sub-district and sub-district institutions can be expected to threaten the political position of regent. Referrals theory suggests that efforts to reposition sub-district can be done through the (a) functional structuralism, (b) redefinition and categorization playroom convenient for sub-district, (c) strengthening human resources in order to invest long-term leadership and with (d) path social-psychological.